Post a New Question

Math

posted by .

Solve for x.

log3(x+7)=2-log3(x-1)

Write the exact answer using base-10 logarithms.

  • Math -

    log3(x+7)=2-log3(x-1)
    log3(x+7) + log3(x-1) = 2
    log3 [(x+7)/(x-1)] = 2
    (x+7)(x-1) = 3^2
    x^2 + 6x - 7 = 9
    x^2 + 6x - 16 = 0
    (x+8)(x-2) = 0
    x = -8 or x = 2

    but x=-8 would make log3(x+7) undefined, so

    x = 2

    ( why would it ask to use base 10 logs ????)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question